REFLEKSI PERSONAL ANXIETY DISORDER MELALUI FOTOGRAFI KONSEPTUAL - Sukmawati, erina; Setiawan, Agus Heru (Institut Seni Indonesia Surakarta, 2021)
ABSTRACTAnxiety disorder is a mental state characterized by excessive fear and uncontrollable anxiety. Nearly everyone has experienced anxiety at various levels. Artwork act as a bridge between human emotion and the psychological problem that could be materialized. In this project, photography is an instrument of documentary likewise conveying the photographer's ideas. The creation of this final project is a reflection of personal experiences that the photographer has been through, then visualized through art media, specifically conceptual photography which focused on the conception. The idea exploration has been achieved by adapting both sources of references and personal experiences, then discover an analysis of the model, tools, and technical equipment to the perceived desired visual presentation. A technical aspect related to this creation of projects is the photography equipment and lighting approach. The aim of this project to deliver that conceptual photography become a media communication for psychological problems and provides knowledge about one of the mental conditions, namely anxiety disorderKeywords: Reflection, personal, anxiety disorder, conceptual photographyABSTRAKAnxiety disorder adalah perasaan cemas yang berlebihan dan merupakan salah satu gangguan mental yang dapat dialami siapa saja. Karya seni merupakan jembatan bagaimana permasalahan yang berhubungan dengan emosi dan psikis seseorang dapat termaterialisasikan. Fotografi sebagai salah satu medium seni, dalam karya ini selain memiliki fungsi dokumentatif, juga memiliki fungsi untuk menyampaikan ide/gagasan seorang fotografer. Penciptaan karya Tugas Akhir ini, merupakan refleksi dari pengalaman personal selama mengalami anxiety disorder, disampaikan melalui media seni, khususnya fotografi konseptual yang fokus pada ide/gagasan. Eksplorasi ide dilakukan dengan menyesuaikan sumber referensi dan pengalaman personal, kemudian mengeksplorasi model dan properti, serta persiapan teknis guna mencapai visual yang diinginkan. Teknis yang berkaitan dengan penciptaan karya ini diantaranya adalah alat dan tata cahaya. Dengan dibuatnya karya ini diharapkan dapat menjadi edukasi bagaimana fotografi konseptual dapat menjadi sarana untuk menyampaikan permasalahan psikologis dan juga menambah wawasan tentang salah satu gangguan mental yaitu anxiety disorder.Kata Kunci: Refleksi, personal, anxiety disorder, fotografi konseptual